Fragmenty tkaniny wełnianej odkrytej w Piotrkowie Trybunalskim, woj. łódzkie - Antosik, Łukasz (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
In 2005, in Piotrków Trybunalski, at 4 Pijarska Street, rescue excavations were conducted by Dr Janusz Pietrzak from the University of Łódź. During the archaeological works, remains of a woollen sack were found. Owing to the fact that both the textile and seeds were discovered in one layer, it is justifiable to assume that the sack was used to store loose materials. The discussed textile remains were found in the layer of an object dated to the period from the mid-16th o the early 17th century. In the 16th century, Piotrków Trybunalski was one of the leading centres of broadcloth industry in the area of the Sieradz Voivodship. At that time, broadcloth production in Piotrków Trybunalski was organized within a guild. In order to protect the selling markets, a ban was introduced in 1532 that prevented foreign merchants from selling cloth of worse quality than the one produced by local craftsmen. Actions intended to control the trade in the town were mainly targeted against rural producers. The analyzed textile could be described as of simple execution. The material for the production of the Piotrków sack is sheep wool. The textile’s weave is tabby. Additionally, partly preserved brocading is found on two fragments of the textile. It cannot be excluded that the discussed textile remains are remains of a sack that was produced of a reused piece of garment, for instance, a coat.